EXISTENTIALISM IN TODD PHILLIPS' JOKER (2019): AN ANALYSIS OF THE MAIN CHARACTER’S SEARCH FOR AUTHENTICITY - Dwiyanti, Anita (Journal of Education, Linguistics, Literature and Language Teaching, 2025)
In today’s media-saturated world, popular films often serve as mirrors reflecting complex philosophical and psychological issues embedded in society. This study explores existentialist themes in Joker (2019), specifically Arthur Fleck's quest for authenticity in an indifferent, chaotic world. Using a critical qualitative literary approach and applying philosophical thematic analysis grounded in Sartrean and Camusian existentialism, the paper examines how Fleck’s experiences of isolation, alienation, and social rejection reflect fundamental existentialist struggle. Through textual and narrative analysis of key scenes for this journal, the study reveals that the social structure of Gotham City is marked by injustice and an imbalance of political views, and that it serves as a trigger for Arthur Fleck's internal conflict, which drives him to a transformation of his identity. This paper contributes to existing literature by emphasizing a philosophical analysis that situates Joker within broader existential discourse.